Destabilizing effect of cannibalism on a structured predator-prey system - 495353 Melisa Amos Makesvaran; Faridah Mustapha; Fakulti Sains (2005)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2005